Mapping groundwater quality Index for irrigation in the Dibdibba aquifer at Karbala - Najaf plateau, central of Iraq - Al-Kubaisi, Qusai Y.; Al-Abadi, Alaa M.; Al-Ghanimy, Maitham A. (Iraqi Journal of Science, 2018)
Mapping groundwater quality Index for irrigation is of great importance for agricultural issues. As groundwater is a vital source of water for domestic and agricultural activities in Iraqi Western Desert area, where the study area (Dibdibba aquifer) represents the extreme eastern part of it, evaluation of groundwater quality and its suitability for irrigation is important. This study aims to develop decision support tools for identifying the optimal locations of groundwater regarding its quality to meet the future demands of the study area. Samples were collected during the wet season (April-May 2017 (and analyzed for determining the physicochemical properties. The indices used in the quality assessment were the sodium adsorption ratio (SAR), sodium percentage (%Na+), magnesium hazard (MH), and irrigation water quality index (IWQI), incorporating the spatial variation using the GIS-based multi-criteria system highlighted the spatial variation of groundwater quality for irrigation in the study area. This spatial distribution indicated that groundwater is generally of moderate quality in the Dibdibba aquifer.